Corpus juris. - Nils Jareborg (Nordisk Tidsskrift for Kriminalvidenskab)
Corpus juris is the outcome of a European Community project, organized by Franceso de Angelis, Director of General Directorate XX (Financial Control). The text, which comprises 35 articles on criminal law and criminal procedure concerning protection of the financial interests of the European Union, was in the final version drafted by Professor Mireille Delmas-Marty (Paris). The most striking feature of the proposal is the establishment of a European Public Prosecutor for crimes of the kind indicated. The article contains a translation of the 35 articles into Swedish and a brief introduction explaining the background, underlining the fact that the proposal is a hurried piece of work.